NILAI-NILAI PENDIDIKAN SEJARAH PERADABAN ISLAM ADIL DAN MODERAT DALAM NOVEL 99 CAHAYA DI LANGIT EROPA KARYA HANUM SALSABIELA RAIS DAN RANGGA ALMAHENDRA - Eviana Eviana (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2015)
The value of education in the history of Islamic civilization is the process of changing children's behavior to be better than the picture of life that will lead to various kinds of analysts from historical stories that are interpreted to the present. The method used in this research is qualitative research with the type of literature study. The fair and moderate value in the novel 99 Cahaya di Langit Europe is a balance between rights and obligations and a balance between the affairs of the world and the hereafter.